A Predicted Mannoprotein Cmp1 Regulates Fungal Virulence in Cryptococcus neoformans - Lian-Tao Han; Lei Wu; Tong-Bao Liu (Pathogens, 2020)
The capsule of the fungal pathogen Cryptococcus neoformans consists of glucuronoxylomannan (GXM), glucuronoxylomannogalactan (GXMGal), and mannoproteins (MPs). MPs are a kind of glycoproteins with low content but high immunogenicity, which can stimulate the immune protection of the host. However, there is not much information about the role of mannoproteins in virulence of the human fungal pathogen C. neoformans. In this study, we reported the identification and functional analysis of a predicted mannoprotein Cmp1 that regulates fungal virulence in C. neoformans. Gene expression pattern analysis indicates that the CMP1 gene was ubiquitously expressed at all stages of cryptococcal development. Subcellular localization analysis indicated that Cmp1 was localized in the cytoplasm of cryptococcal cells. Disruption or overexpression of CMP1 results in impairing capsule formation in Cryptococcus, but it does not affect the melanin production and sensitivity under various stress conditions, nor does it affect the sexual reproduction process of Cryptococcus. Survival assay showed that the pathogenicity of the cmp1Δ mutant or the CMP1 overexpression strain was significantly attenuated in a murine inhalation model of cryptococcosis. In conclusion, our findings implied that the mannoprotein Cmp1 is required for the virulence of C. neoformans.